Prof. dr hab. Jerzy Prochorow (1938-2006) siedlczanin z urodzenia - MIODUSKA, Agnieszka (Historia i Świat, 2015)
Assosiate Professor Jerzy Prochorow was born and brought up in Siedlce. He connected his scientific thesis with the Institute of Physics of Polish Academy of Science, where he obtained the degree of PhD and PhD with habilitation, later the academic title – Professor of Physical Science. He worked as a director of Institute of Physics (PAS), the chairman of Scientific Council (IF PAS). He was also a member of Scientific Council IF PAS for a long time. He received scientific awards for his work and activity.